DESAIN PEMBELAJARAN MATERI OPERASI PADA HIMPUNAN MENGGUNAKAN PERMAINAN â€œLEMON NIPISâ€ - Mumu, Jeinne; Tanujaya, Benidiktus (Universitas Papua, 2018)
This research aims to design student learning activities on the concept of sets, especially operations on the sets. The research was conducted by using design research method with a mathematics realistic education approach. The subjects of this study are 42 students of mathematics education at the University of Papua taking lecture of realistic mathematics education. There are three stages in the implementation of this research, namely preliminary design, experimental design, and retrospective analysis. The results of the study show that the use of game